Interventions to mitigate drug shortages in public health systems in sub-Saharan Africa: a scoping review protocol - Constance Sewani-Rusike; Busisiwe Mrara; Olubunmi Margaret Ogbodu (BMJ Open)
Introduction Globally, drug shortages affect low-, middle- and high-income countries to different degrees. The challenges associated with drug shortages in health systems, particularly in public health facilities, and the consequent multiple adverse effects on patients and the health systems have led countries to continue to explore and implement different strategies to combat this challenge. Various factors implicated in drug shortages range from manufacturing concerns, demand issues, supply chain disruptions and regulatory issues. The effects of drug shortages in health systems range from poor patient compliance and therapeutic failure to antimicrobial resistance, low morale among healthcare workers and public distrust in government services. Furthermore, the effects of drug shortages in public health facilities include unavailability of drugs to patients, hospitalisation and readmissions, and associated costs that could be avoided, high out-of-pocket expenditures suffered by patients as patients resort to buying drugs from private pharmacies where the prices are usually exorbitant and prohibitive, putting patients at risk of treatment default due to lack of affordability. Successful mitigation strategies deployed to prevent and manage drug shortages in sub-Saharan Africa (SSA) remain unshared despite the potential of these strategies to serve as valuable lessons if the evidence is scientifically synthesised and reported. The scoping review will synthesise evidence to provide policy guidance for better planning of health services and resources, resulting in improved quality of life for citizens, underscoring the importance of functional and responsive health systems.Methods and analysis Using the Joanna Briggs Institute (JBI) scoping review methodology, a five-stage review is outlined: (1) determining the research question, (2) search strategy, (3) inclusion criteria, (4) data extraction and (5) analysis and presentation of the results. The literature search will use PubMed, SCOPUS and the Elsevier Science Direct search interfaces, reflecting empirical and grey literature. We will focus on literature published between 2000 and 2025. The study start and end dates are 1 September–30 November 2025. A two-stage screening process will be used to determine the eligibility of articles. All articles will be individually assessed for eligibility by two reviewers, while a third reviewer will resolve any disagreements. The data from eligible articles will be extracted and charted using a standardised form. Extracted data will be analysed using narrative and descriptive analyses.Ethics and dissemination Ethical approval is not required for this scoping review as it will use only previously published data. It does not require human participation. The results of this search will be disseminated through academic presentations at conferences and peer-reviewed publications.